Report of the Committee to review and Rationalise Centrally Sponsored Schemes for Poverty Alleviation and Employment Generation - (:unkn) unknown (Planning Commission Government of India, 1980)
The Committee’s report, commissioned by the Planning Commission, evaluates Centrally Sponsored Schemes for poverty alleviation and employment generation in India, aiming to streamline and enhance their effectiveness. Key recommendations focus on rationalizing self-employment schemes, such as the Integrated Rural Development Programme (IRDP), by standardizing subsidies and promoting group-based project implementation. Training initiatives like TRYSEM are proposed for integration to strengthen skill development, while DWCRA emphasizes women’s empowerment through collective income-generating activities. For urban areas, consolidation of Nehru Rozgar Yojana (NRY) and Urban Micro Enterprises (SUME) into unified programs is recommended to simplify access and standardize project costs. The report also addresses Prime Minister Rozgar Yojana (PMRY), Khadi and Village Industries Commission (KVIC), and National Finance and Development Corporations, suggesting enhanced funding limits, streamlined processes, and unified funding patterns between Centre and States. Additional recommendations include reducing duplication among implementing agencies, creating a guarantee fund for credit-linked self-employment schemes, and establishing a comprehensive beneficiary database to ensure targeted assistance. The report underscores that consolidating and standardizing these schemes can improve operational efficiency, expand outreach, and provide sustainable economic opportunities to the most vulnerable populations in both rural and urban India.
Government of India Planning Commission April 1997
Keywords: Poverty Alleviation; Employment Generation; Centrally Sponsored Schemes; IRDP; PMRY; NRY; Urban Micro Enterprises; DWCRA; KVIC; Subsidy Standardization; Self-Employment; Scheme Rationalization